Essential Oil from Myrica rubra Leaves Potentiated Antiproliferative and Prooxidative Effect of Doxorubicin and its Accumulation in Intestinal Cancer Cells - Ambrož, Martin; Hanušová, Veronika; Skarka, Adam; Boušová, Iva; Králová, Věra; Langhasová, Lenka; Skálová, Lenka (Planta medica, 2016)
Essential oil from the leaves of Myrica rubra, a subtropical Asian fruit tree traditionally used in folk medicines, has a significant antiproliferative effect in several intestinal cancer cell lines. Doxorubicin belongs to the most important cytostatics used in cancer therapy. The present study was designed to evaluate the effects of defined essential oil from M. rubra leaves on efficacy, prooxidative effect, and accumulation of doxorubicin in cancer cell lines and in non-cancerous cells. For this purpose, intestinal adenocarcinoma CaCo2 cells were used. Human fibroblasts (periodontal ligament) and a primary culture of rat hepatocytes served as models of non-cancerous cells. The results showed that the sole essential oil from M. rubra has a strong prooxidative effect in cancer cells while it acts as a mild antioxidant in hepatocytes. Combined with doxorubicin, the essential oil enhanced the antiproliferative and prooxidative effects of doxorubicin in cancer cells. At higher concentrations, synergism of doxorubicin and essential oil from M. rubra was proved. In non-cancerous cells, the essential oil did not affect the toxicity of doxorubicin and the doxorubicin-mediated reactive oxygen species formation. The essential oil increased the intracellular concentration of doxorubicin and enhanced selectively the doxorubicin accumulation in nuclei of cancer cells. Taken together, essential oil from M. rubra leaves could be able to improve the doxorubicin efficacy in cancer cells due to an increased reactive oxygen species production, and the doxorubicin accumulation in nuclei of cancer cells.
Keywords: doxorubicin; Myrica; reaktivní formy kyslíku; Cells, Cultured; lidé; Caco-2 Cells; Cell Proliferation; Drug Synergism; hepatocyty; Caco-2 buňky; krysa rodu Rattus; střevní nádory; oleje prchavé; Doxorubicin; kultivované buňky; Humans; Hepatocytes; rostlinné extrakty; potkani Wistar; proliferace buněk; Intestinal Neoplasms; Antineoplastic Agents, Phytogenic; Rats, Wistar; mužské pohlaví; synergismus léků; fytogenní protinádorové látky; zvířata; Rats; Animals; Plant Extracts; Reactive Oxygen Species; Male; Oils, Volatile